Comprehensive analysis of the meanings of being pregnant and having HIV/aids - Andressa Guimarães Machado; Stella Maris de Mello Padoin; Cristiane Cardoso de Paula; Letícia Becker Vieira; Dilce Rejane Peres do Carmo (Rev Rene)
Reported cases of AIDS in women resulted in an investment in the prevention of vertical transmission and maternal and child care to reduce morbidity and mortality. This research aimed to understand the meanings of being pregnant and having HIV/AIDS. Interviews were developed with seven women between March/April 2009. The setting was a university hospital in Santa Maria / RS / Brazil. A qualitative research with phenomenological approach was carried out through the method of comprehensive analysis by Martin Heidegger. The method revealed the difficulty in finding out the diagnosis, the fear of transmitting the virus to their children and not being able to nurture them, and die. These women describe experiences of other pregnancies and unplanned pregnancies. They are aware of the prejudice, so that the family does not know about the diagnosis. The results confirmed the necessity of thinking about health practices in order to develop in the daily care an empathic listening that seeks to understand the experiences and needs of the women and their families.